Traditional Islamic education in Asia and Africa: a comparative study of Malaysia’s Pondok, Indonesia’s Pesantren and Nigeria’s traditional madrasah - Hashim, Rosnani; Ahmad Rufai, Saheed; Mohd Nor, Mohd Roslan (IDOSI, 2011)
The Muslim world has witnessed the emergence of several Islamic-based institutes and universities in the last three decades, in keeping with some of the recommendations of World Conferences on Muslim Education. Such a development has greatly improved the quality of higher Islamic education especially with regards to the contribution to Islamic scholarship of some of the graduates of such Islamic institutes and universities. However, the traditional system of Islamic education at the pre-university level has not been greatly influenced by such a development. There has not been a comprehensive study of the system as operated in various contemporary Muslim settings, with a view to assessing the degree of its efficacy. Therefore, there is a long-felt need for such a research endeavour. The purpose of this paper is to carry out a comparative study of Malaysia’s pondok, Indonesia’s pesantren and Nigeria’s traditional madrasah system. The choice of the three educational settings was informed by the growing impression that Malaysia and Indonesia, both Asian countries, offer some of the best practices in traditional Islamic education, which may be used as standards in improving upon what operates in Nigeria, an African country with the largest Muslim population and largest number of madaaris (pl.). The paper traces the origins of the traditional Islamic education system, discusses the evolution of each of the three systems and addresses such salient issues as ownership of the school, the structure of the school, the curriculum, teachers’ requirements and qualifications, teaching methods, evaluation procedures, teachers’ welfare and salaries, the socio-economic status of the teacher, the schools and the challenges of higher education in the face of urbanization, as well as practical recommendations for reforms. The paper, which is both historical and analytical in nature, employs the philosophical method, in its critical perspectives and practical suggestions. The significance of such a comparative study lies in its potentiality to expose the strengths and deficiencies of each of the educational settings, as well as highlight their commonalities and differences.